Evaluación de la producción de residuos sólidos hospitalarios en el hospital Essalud – I de la ciudad de Moyobamba - Villacorta Paredes, Jessica (2014)
In this Thesis Project production was determined by weight of the sol id waste, has underlined its volume, its density was determined and its composition was evaluated and 1 or characterize the solid waste generated during the 24 hours of the six (6) specialized areas (lnpatient, outpatient, laboratory, delivery room, operating room and emergency) ESSALUD Hospital - 1 Moyobamba City, District and Province of Tumbes. The collection of solid waste produced during 24 hours in three shifts, with the support of the housekeeping staff was conducted; 6 bags daily one for each area, and then be you translate to collection point where the corresponding study was performed to obtain the weight, density, volume and composition of solid waste to be collected subsequently analyzed, taking into account established in the Technical Standard for Hospital Solid Waste Management - NT -MI NSNDGSP Vol 1. The results obtained are: The study of the solid waste generated in the Hospital ESSALUD - 1 City of Tumbes, it was determined that production by weight of solid waste is 7.61 kg 1 service 1 day, volume is 12.23 L 1 service 1 day its density is 0.16 kg/ L and solid wastes are composed of cardboard, paper, fabric, wood, hard plastic, plastic bags and wraps, metals, plaster casts, bandages, swabs and diapers, food waste and fruits, infusion, gloves, masks and league; culture media; glasses; land and other and unknown; which the group of gauze, cotton and diapers is having highest percentage 32.35%, equivalent to 129.45 kg.